Case report: Periventricular heterotopia and early-onset bipolar disorder in adolescent patient with history of childhood attention deficit hyperactivity disorder - Cho, Seo-Hyun; Lee, Ju-Yeon; Kim, Honey; Kim, Sung-Wan; Kim, Jae-Min; Shin, Il-Seon (Frontiers in Psychiatry, 2024)
Periventricular heterotopia (PH) is a developmental malformation in the brain. Because the clinical symptoms are heterogeneous, few studies have investigated the psychiatric symptoms associated with PH. We describe the case of a 17-year-old male with bipolar disorder (BD), who had been treated for attention deficit-hyperactivity disorder (ADHD) and developmental delay in childhood. He had experienced depression for 1 year and was admitted to the emergency room following a suicide attempt. He was admitted to the psychiatric ward for further evaluation and treatment for elated mood, decreased need for sleep, increased sexuality, and delusion. The patient was diagnosed with BP-I disorder and PH via brain magnetic resonance imaging. After combined treatment with valproic acid and aripiprazole, his manic symptoms stabilized. To our knowledge, this is the first report of an adolescent PH case with a history of early onset BD and ADHD in childhood.